FORMAÇÃO DOCENTE E PRÁTICA PEDAGÓGICA DOS PROFESSORES DE EDUCAÇÃO FÍSICA: UMA ANÁLISE DAS RELAÇÕES NO CONTEXTO ESCOLAR - Melo, Luiz Gonzaga de (2012)
This thesis presents an analysis of the relations between the physical education teacher‟s pedagogical practice, their instruction as a teacher and the Curricular Guidelines of Basic Education concerning Physical Education – CGE (PARANÁ, 2008). The goal of this research was analyzing the converging and diverging points between the physical education teacher‟s pedagogical practice, their formation as a teacher and the CGE of Physical Education (Paraná, 2008). The research is characterized as qualitative. The scientific - theoretical presuppositions which guide this work are the historical-cultural and the historical-critical pedagogy, since these are also the presuppositions that give base to the aforementioned CGE (Paraná, 2008). It was used as theoretical basis the contributions by researchers who discuss questions related to the education, physical education and the formation of teachers, permeating them with reviews and proposals. (PIMENTA, 1994; SAVIANI, 1986; TARDIF, 2000; PÉREZ GÓMEZ, 2000; BRACHT; ALMEIDA, 2006; IMBERNÓN, 2007; TAFFAREL et al., 2007; VEIGA, 2009; GATTI, 2010; BEHRENS; PEREIRA, 2011). The research involved the analysis of the context of the pedagogical practice of nine (09) Physical Education teachers, who work in four (04) State Public Schools of the municipality of Ibaiti – PR. The tools utilized in the research in order to collect data were the observations of the classes, the application of questionnaires and also interviews with Physical Education teachers. As a methodological option, it‟s been chosen the Triangulation of data (TRIVIÑOS, 2008) and the Analysis of Content (BARDIN, 1977). The results of the research indicate that : a) the divergences are greater than the convergences between teacher‟s pedagogical practice and their formation as teachers and the CGE (PARANÁ, 2008); b) the initial formation of the teachers , as well as the programs of continuous formation which are offered by the State Department of Education SEED/PR, do not comply with the CGE – EF (PARANÁ, 2008) or are insufficient to provide the teacher with a training that enables them to comprehend and put into practice the proposals of the CGE; c) the initial formation of the teacher is much more guided towards technicist practices and the needs of the market, neglecting the classroom practices, or else, “it doesn‟t teach to be teacher”; d) the pedagogy of Physical Education in school reveals a characteristic which tends towards sports, which can be understood as a result of the the trajectory of the teachers as athletes, as well as well as of the academic formation focused on sports that they had; e) there is an ignorance from the teachers concerning the theoretical presuppositions, goals, elements, methodology and assessment criteria found in the CGE (PARANÁ, 2008). Although the research carried out has tried to analyze the converging and diverging points between the teacher‟s pedagogical practice, their formation as teachers and the CGE of Physical Education (PARANÁ, 2008), many aspects related to the pedagogical practice, the formation of the teachers and the curricular guidelines still need to be further analyzed and discussed.